KAJIAN SPASIAL AKSESIBILITAS PADA PERENCANAAN KAWASAN KAMPUS UNIVERSITAS KEBANGSAAN REPUBLIK INDONESIA - Karto Wijaya; Dony Hendriawansyah; Faun Nurrokhman (Jurnal Arsitektur ARCADE, 2025)
Abstract: Accessibility is an important aspect of a comfortable, functional, and supportive environment for human activities. The quality of accessibility of a public space, such as a university area, greatly affects social interaction, mobility, and the efficiency of space use. In the context of spatial planning and development, a deep understanding of the characteristics and performance of accessibility of an area is very important. Improving the quality of the campus environment is an important aspect in supporting academic and non-academic activities in higher education institutions. This study focuses on the spatial study of accessibility in the development of the National University of the Republic of Indonesia campus area in Lingkar Selatan Village, Bandung City, using space syntax analysis. The approach applied in this study is descriptive quantitative and is carried out spatially, where the research method utilizes Space Syntax software. In the analysis of the road network in the development area of ​​the National University of the Republic of Indonesia campus, an R² value of 0.799165 was obtained. With the location of the National University of the Republic of Indonesia Campus development area near the main access road, it can be concluded that the main road network on Jalan Pelajar Pejuang 45 and Jalan Talaga Bodas has a road connectivity value with a high level of spatial integrity. This means that the main road structure located in the development area of ​​the National University of the Republic of Indonesia Campus provides easy access in creating good proximity between various spaces in the area. Keyword: Space Syntax, accessibility, spatial space, connectivity Abstrak: Aksesibilitas merupakan hal penting terhadap lingkungan yang nyaman, fungsional, dan mendukung aktivitas manusia. Kualitas aksesibilitas suatu ruang publik, seperti kawasan universitas, sangat mempengaruhi interaksi sosial, mobilitas, serta efisiensi penggunaan ruang. Dalam konteks perencanaan dan pengembangan ruang, pemahaman mendalam mengenai karakteristik dan kinerja aksesibilitas suatu kawasan menjadi sangat penting. Peningkatan kualitas lingkungan kampus merupakan aspek penting dalam mendukung aktivitas akademik dan juga non-akademik pada institusi pendidikan tinggi. Penelitian ini berfokus pada kajian spasial aksesibilitas dalam pengembangan kawasan kampus Universitas Kebangsaan Republik Indonesia di Kelurahan Lingkar Selatan, Kota Bandung, dengan menggunakan analisis space syntax. Pendekatan yang diterapkan dalam studi ini bersifat deskriptif kuantitatif dan dilakukan secara spasial, di mana metode penelitiannya memanfaatkan perangkat lunak Space Syntax. Dalam analisis jaringan jalan pada kawasan pengembangan kampus Universitas Kebangsaan Republik Indonesia, didapatkan nilai R² sebesar 0,799165. Dengan letaknya kawasan pengembangan Kampus Universtitas Kebangsaan Republik Indonesia ini berada dekat jalan akses utama dapat disimpulkan bahwa jaringan jalan utama pada jalan Pelajar Pejuang 45 dan jalan Talaga Bodas memiliki nilai Konektivitas jalan dengan tingkat integritas ruang yang tinggi. Artinya, struktur jalan utama yang berada pada kawasan pengembangan Kampus Universitas Kebangsaan Republik Indonesia ini memberikan akses kemudahan dalam menciptakan kedetakan yang baik antara berbagai ruang di kawasan. Kata Kunci: Space Syntax, aksesibilitas, spasial ruang, konektivitas